2020
DOI: 10.1145/3398069
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning in Mental Health

Abstract: High prevalence of mental illness and the need for effective mental health care, combined with recent advances in AI, has led to an increase in explorations of how the field of machine learning (ML) can assist in the detection, diagnosis and treatment of mental health problems. ML techniques can potentially offer new routes for learning patterns of human behavior; identifying mental health symptoms and risk factors; developing predictions about disease progression; and personalizing and optimizing therapies. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(72 citation statements)
references
References 187 publications
0
46
0
1
Order By: Relevance
“…Building upon the overall positive and negative developments above, we apply a principle-based ethical framework for CBT chatbots, taking stock from previous work that has also employed normative principles. We found pertinence in the principles of beneficence, non-maleficence, autonomy, justice, and explicability-previously used in a typology for AI-ethics in general (29); and in the structure of findings from a systematic review of machine learning for mental health (30). Despite the relevance of these previous works, they are not sufficient to attend to the particularities of CBT chatbots, which demands discussions of the appropriateness of artificially produced therapeutic alliances, for instance.…”
Section: Applying An Ethical Frameworkmentioning
confidence: 85%
See 1 more Smart Citation
“…Building upon the overall positive and negative developments above, we apply a principle-based ethical framework for CBT chatbots, taking stock from previous work that has also employed normative principles. We found pertinence in the principles of beneficence, non-maleficence, autonomy, justice, and explicability-previously used in a typology for AI-ethics in general (29); and in the structure of findings from a systematic review of machine learning for mental health (30). Despite the relevance of these previous works, they are not sufficient to attend to the particularities of CBT chatbots, which demands discussions of the appropriateness of artificially produced therapeutic alliances, for instance.…”
Section: Applying An Ethical Frameworkmentioning
confidence: 85%
“…To better attend to the principle of non-maleficence, a thorough analysis of potential risks to mental and physical integrity, dignity, and safety needs to be conducted (30). Ethical professionals' engagement in defining the appropriate boundaries of personalised care using digital tools should be a minimum requirement (62); and vulnerable persons should be consulted during design, development, and deployment (63).…”
Section: Discussionmentioning
confidence: 99%
“…The passively sensed data could be complemented and improved with actively collected data via self-reporting solutions such as ecological momentary assessments [27]. However, as Thieme et al [79] have indicated in their review of ML in mental health, much work is needed in understanding what data individuals are willing to share passively and actively to design appropriately responsive ML driven mental health technologies. Our fndings show that UMY have high privacy concerns.…”
Section: Designing For the Micro-systemsmentioning
confidence: 99%
“…With respect to the application in psychology, classification algorithms have been proven to be highly effective to predict participants' mental status. A recent systematic review summarized the application of machine learning in the area of mental health and suggested that the performance of classification algorithms was satisfied in the prediction of depression, suicide, job-related stress, bipolar disorder, mood, posttraumatic stress disorder, anxiety, substance abuse, and schizophrenia (Thieme et al, 2020). According to the "No Free Lunch Theorem", no single algorithm is consistently superior to the others (Wolpert & Macready, 1997).…”
Section: Introductionmentioning
confidence: 99%